1997
DOI: 10.1177/0146167297232005
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Seff-Perceptions: Convergent Evidence from Three Measures of Accuracy and Bias

Abstract: This research assessed gender differences in the accuracy of self-perceptions. Do males and females with equal ability have similar self-perceptions of their ability? Three measures of accuracy were used: accuracy of self-evaluations, calibration for individual questions, and response bias. As hypothesized, for a masculine task, significant gender differences were found for all three measures: Females' self-evaluations of performance were inaccurately low, their confidence statements for individual questions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
206
1
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 405 publications
(233 citation statements)
references
References 72 publications
18
206
1
8
Order By: Relevance
“…7 One third of the participants are principals, the remaining two thirds are agents. Participants are randomly matched into groups of three, where each group consists of one principal and two agents.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…7 One third of the participants are principals, the remaining two thirds are agents. Participants are randomly matched into groups of three, where each group consists of one principal and two agents.…”
Section: Experimental Designmentioning
confidence: 99%
“…We chose the number-adding task as performance depends not only on effort but also on ability. 9 Furthermore, the task is easy to understand 7 The experiment was framed neutrally. While we refer to "principals" and "agents" in the following, we used the neutral terms participant A and B to describe the roles in the experiment.…”
Section: Experimental Designmentioning
confidence: 99%
“…Moreover, Rosenthal et al (1996) argue it may be 'proper female modesty' accounting for the underrating by female managers. Beyer (1990Beyer ( , 1998 and Beyer and Bowden (1997) argue that when (managerial) tasks and roles are perceived as more masculine than feminine, women are more likely than men to underestimate their competencies in these areas. Along these lines, several studies show that managers are perceived to have characteristics more commonly associated with men than with women (Schein, 1973 andButterfield, 1979 and.…”
Section: Gender and Self-perceptions In Business And Entrepreneurshipmentioning
confidence: 99%
“…While many studies have focused on self-assessment of IQ or other intelligence measures (Beyer and Bowden 1997, Beyer 1990, Furnham 2001, Furnham et al 2002, similar effects have been observed in work performance reviews and many other domains (Beyer 1990, Beyer et al 2003, Blanch et al 2008. This difference seems to stem, in part, from social pressure for female modesty (Furnham et al 2002), coupled with a lower self-attribution bias among women, in that they are less likely to falsely attribute their success to their own efforts (Beyer 1990, Miller andRoss 1975).…”
Section: Persistence and The Founding Gapmentioning
confidence: 84%
“…The "male hubris, female humility" effect has been repeatedly identified in many studies and contexts: men consistently overestimate their own abilities while women consistently underestimate theirs (Beyer and Bowden 1997, Beyer 1990, 1998, Cross and Madson 1997, Furnham et al 2002. These findings have been shown to be "universal" across multiple cultures (Furnham et al 2002).…”
Section: Persistence and The Founding Gapmentioning
confidence: 92%